(untitled) (Kindle, 2022)
Between the end of the last century and the initiation of this one, blood groups and their importance have been increasingly assessed and reported about. In addition to scientific investigations, popular curiosity is also increasing. Most of the investigation is based on phenotypic divisions of blood groups and primarily associated with the ABO system. This is the most significant blood group system in transfusion and transplantation medicine, as it represents an immunological barrier against incompatible blood transfusions or transplantation of incompatible tissues. The clinical significance of antibodies to the ABO system is due to the natural presence of such antibodies and their high function, which can be the reason for hemolytic transfusion reactions, hemolytic disease of the newborn and rejection of the transplanted tissues. The frequency of ABO alleles in different populations is not the same, and many investigations have reported an association between the occurrence of some disorders with different genotypes of ABO blood groups.